(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The A. focus the inscription in Lusitanian language recently found in Arronches (Portugal). From a direct analysis of the stela, he reviews its reading, presenting a new interpretation. This one considers that theonimic designations precede those of the sacrificial animals and not the opposite. The A. concludes that the invocative text is organized as followed: (a) a consecration to a “triform” goddess who receives three animals; (b) a “trifunctional” textual block devoted to three deities, culminating with Reva who receives tauro ifate; (c) a textual block devoted to Bandi and Munitie, the two main tutelary deities of the Galaico-Lusitanian area. Then, it follows the complementary text, which contains the personal names and the generic designation of the cultores — ougurani — as well as references to the ritualistic circumstances.